Mashadirul Ahkam: As-Sunnah As A Source Of Islamic Law - Sabli, Yeni Fatma; Umar, M. Hasbi; Adawiyah, Robi’atul (El-Ghiroh : Jurnal Studi Keislaman, 2025)
This study aims to explore the concept of Mashadirul Ahkam, with a particular focus on As-Sunnah as a fundamental source of Islamic law. The research employs a qualitative approach, utilizing library-based methods to collect and analyze both primary and secondary sources. Primary sources include the Qur'an and canonical collections of Hadith, such as Sahih Bukhari and Sahih Muslim, which are critically examined to understand how As-Sunnah complements and elucidates the legal principles outlined in the Qur'an. Additionally, the works of classical scholars, including Imam Shafi'i, are analyzed to highlight their contributions to the theory of As-Sunnah as a legal source. The study also incorporates contemporary interpretations by modern Islamic jurists to provide insights into the evolution of the understanding of As-Sunnah and its application in addressing contemporary issues. A comparative analysis is conducted to explore differences in interpretation across various Islamic schools of thought. The findings are organized thematically, focusing on key themes such as the authority of As-Sunnah, its role in legal derivation, and its interplay with other sources of Islamic law. The results indicate that As-Sunnah plays a crucial role in specifying and contextualizing the general laws found in the Qur'an, thereby enhancing the understanding and application of Islamic law in everyday life. This research underscores the enduring relevance of As-Sunnah in Islamic legal theory and its significance in guiding Muslims in their religious practices. Ultimately, the study contributes to a deeper understanding of the sources of Islamic law and their implications for contemporary Islamic jurisprudence.